Cognitive behavioural therapy for tinnitus - Fuller, Thomas (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects and safety of CBT for tinnitus in adults.